2016
DOI: 10.1177/1062860615612923
|View full text |Cite
|
Sign up to set email alerts
|

Shift-to-Shift Handoff Effects on Patient Safety and Outcomes

Abstract: Multiple health care organizations have identified handoffs as a source of clinical errors; however, few studies have linked handoff interventions to improved patient outcomes. This systematic review of English-language research articles, published January 2008 to May 2015 and focusing on shift-to-shift handoff interventions and patient outcomes, yielded 10 774 unique articles. Twenty-one articles met inclusion criteria, measuring each of the following: patient falls (n = 7), reportable events (n = 6), length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 49 publications
(279 reference statements)
3
74
0
Order By: Relevance
“…As emerged from the quality assessment of the included reviews, most checklist items were satisfied as reported in Table S2. According to the findings, an effective handover promotes better patient outcomes (Mardis et al, , ; Sherman, Sand‐Jecklin, & Johnson, ) and has great importance for PS (Buus et al, ) especially in postoperative care (Møller et al, ) and in the intensive care unit where patients are vulnerable because of their complex clinical history and the critical nature of their conditions (Colvin et al, ). NHs are also important as a system to guarantee professional support (e.g., Holly & Poletick, ; Matic et al, ) and continuity of care (e.g., Buus et al, ; Smeulers et al, ) where barriers affecting the quality of communication can have multiple consequence, both on PS and professionals (e.g., Halm, ; Riesenberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As emerged from the quality assessment of the included reviews, most checklist items were satisfied as reported in Table S2. According to the findings, an effective handover promotes better patient outcomes (Mardis et al, , ; Sherman, Sand‐Jecklin, & Johnson, ) and has great importance for PS (Buus et al, ) especially in postoperative care (Møller et al, ) and in the intensive care unit where patients are vulnerable because of their complex clinical history and the critical nature of their conditions (Colvin et al, ). NHs are also important as a system to guarantee professional support (e.g., Holly & Poletick, ; Matic et al, ) and continuity of care (e.g., Buus et al, ; Smeulers et al, ) where barriers affecting the quality of communication can have multiple consequence, both on PS and professionals (e.g., Halm, ; Riesenberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 16 reviews have reported suggestions for future research (Table ) highlighting this field as a priority (Colvin et al, ) as well as stressing the need to increase funding for handover studies, especially those measuring patient outcomes (Mardis et al, ). Among the research lines suggested, reviews highlighted the need to develop studies aimed at detecting the best method to provide reliable and valid data (Matic et al, ), along with the effectiveness of standardized handovers (Colvin et al, ; Mardis et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To transfer essential information and responsibility for patient care from one health care provider to another (a practice commonly referred as handover) is an integral component of communication in healthcare setting (ACSQHC, 2005;Ong & Coiera, 2011;Mardis et al, 2015). Clinical handover is the transfer of professional responsibility and accountability for some or all aspects of care for a patient, or group of patients, to another person or professional group on a temporary or permanent basis (ACSQHC, 2009;ACSQHC, 2011).…”
Section: Introductionmentioning
confidence: 99%